Model Integrated Disease Management to facilitate effective translatable solutions for wildlife disease issues. Issue 12 (30th September 2022) - Carver, Scott; Peters, Andrew; Richards, Shane A.
Abstract: There are multiple demands for the development of effective and sustainable disease management practices in wildlife, but solutions are widely lacking. In this perspective, we focus on the need to structure research to support advancement toward enhanced wildlife disease control solutions. We concentrate on the need for improved integration between wildlife disease management undertaken in situ with modelling to guide and assess disease management actions. We recognise that many disease management attempts in wildlife are made in isolation, are not supported by modelling and are not used as a stepping stone to advancement. However, we emphasise that the development of disease control practices in wildlife is greater than any one management attempt, and should be seen and undertaken as a set of systematic steps towards well‐articulated management goals. We describe modelling of disease management and in situ disease management as two complementary phases of investigation, viewed as a feedback loop to support advancements, and highlight established and less established pathways in this loop. We describe how stakeholders engaged in practical management actions can better engage with modellers, and also the need for more fit‐for‐purpose modelling that captures the on‐ground realities of in situ practice to support advancements. The concepts and approaches described in this perspective are captured within a Model Integrated Disease Management for wildlife framework. We illustrate the framework, concepts and challenges proposed in this perspective using a case study for which we have experience: sarcoptic mange (etiologic agent Sarcoptes scabiei ) in bare‐nosed wombats ( Vombatus ursinus ). Synthesis and applications : Effective and sustainable solutions to critical wildlife diseases are needed. Progress can be improved when disease management is guided through iterative and fit‐for‐purpose integration between modelling and in situ practice. We describe and illustrate a Model Integrated Disease Management for wildlife framework. Moving beyond isolated disease management attempts into a structured process of advancement can help overcome barriers to tackling pathogens threatening wildlife. Abstract : Effective and sustainable solutions to critical wildlife diseases are needed. Progress can be improved when disease management is guided through iterative and fit‐for‐purpose integration between modelling and in situ practice. We describe and illustrate a Model Integrated Disease Management for wildlife framework. Moving beyond isolated disease management attempts into a structured process of advancement can help overcome barriers to tackling pathogens threatening wildlife.